CONCEPTUAL PROVISIONS FOR THE FORMATION OF THE CADASTRE OF INTELLECTUAL RESOURCES AS PART OF THE CENTER FOR THE PROCESSING OF CADASTRAL AND OTHER ADDITIONAL INFORMATION - Pilicheva, M.; Domareva, S. (Municipal economy of cities. Series: «Economy science», 2025)
Modernization of cadastral systems is a continuous process that corresponds to dynamic changes in society and technology. Studying international experience allows us to identify promising areas of development and implementation of innovative solutions in the field of land cadastre. Particular attention is paid to the issues of integrating cadastral systems with other information resources and ensuring the accuracy of geospatial data. This article presents a comparative analysis of the cadastral systems in Ukraine and Switzerland to identify opportunities for improving the Ukrainian land cadastre. The study examines the legal framework, functional purpose, technical characteristics, and financing aspects of both systems. Based on an analysis of Swiss experience, recommendations for modernizing Ukraine’s cadastral system are proposed, including the implementation of decentralized management elements, enhancement of technical infrastructure, and optimization of the financial model. The research highlights the fundamental differences in the cadastral structures of both countries. The Swiss cadastre operates as a decentralized system with significant regional autonomy, ensuring high data accuracy and integration with various geospatial resources. Meanwhile, the Ukrainian cadastral system follows a centralized model, which facilitates uniformity in land registration but faces challenges in data updating and interregional cooperation. The study underscores the importance of implementing 3D cadastres, improving the accessibility of cadastral data, and integrating public-law restrictions into the system, as exemplified by Switzerland. The financial mechanisms supporting the Swiss cadastre are analyzed, emphasizing the advantages of a mixed funding model that combines public financing with elements of self-sufficiency. In contrast, Ukraine relies primarily on state funding, which limits its ability to introduce innovative solutions. The article suggests that adapting Switzerland’s financing approach could improve the efficiency and sustainability of Ukraine’s cadastral system. The study concludes that adopting best practices from Switzerland – such as a more flexible regulatory framework, enhanced geospatial data integration, and diversified financial support – can significantly contribute to the modernization of Ukraine’s land cadastre. Implementing these measures will enhance transparency, facilitate more efficient land management, and improve the overall quality of cadastral services.